2020
DOI: 10.1111/jomf.12637
|View full text |Cite
|
Sign up to set email alerts
|

Family Processes and Children's and Adolescents' Well‐Being

Abstract: The primary purpose of this review was to examine theory and research published during the past decade that focused on family processes and children's and adolescents' well‐being. Scholarship focused on family processes and child and adolescent well‐being made significant and exciting advances during this decade based on several key advancements. In addition to a brief introduction and a conclusion, this decade in review is organized into four sections. In the first section, advances made in the literature bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 200 publications
(242 reference statements)
3
67
0
7
Order By: Relevance
“…Regarding this finding, some authors have proposed a link between the victim's gender and gender roles (Cottrell and Monk, 2004;Gallagher, 2004;Cortina and Martín, 2020). Thus, it is possible that the incorporation of women to the labor market, along with a dynamic flexible family model (Buehler, 2020), may contribute to a parity between mothers and fathers as victims (Williams et al, 2017). Furthermore, the blurring of gender roles in adolescents in comparison to traditional gender roles of the past may also play a key role.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this finding, some authors have proposed a link between the victim's gender and gender roles (Cottrell and Monk, 2004;Gallagher, 2004;Cortina and Martín, 2020). Thus, it is possible that the incorporation of women to the labor market, along with a dynamic flexible family model (Buehler, 2020), may contribute to a parity between mothers and fathers as victims (Williams et al, 2017). Furthermore, the blurring of gender roles in adolescents in comparison to traditional gender roles of the past may also play a key role.…”
Section: Discussionmentioning
confidence: 99%
“…When children grow up in unstable contexts with high levels of stress, outcomes can be worse (Buehler, ; Umberson, & Thomeer, ). New research has shown associations between repeated income shocks and reduced educational engagement and between instability and food insecurity as well as reduced educational achievement in adulthood, especially for children in low‐income families (Gennetian, Wolf, Hill, & Morris, ; B. L. Hardy, ; Wolf & Morrissey, ).…”
Section: New Mechanismsmentioning
confidence: 99%
“…Studies of family process can shed light on the interactions that occur among family members as they communicate with and relate to one another, including offering support and affection as well as neglect and aggression (Buehler, 2020). To better understand how families influence adolescent sexual development and well-being, researchers have mostly examined the quality of parent-child relationships.…”
Section: Adolescent and Family Process In Relationships: Variations And Contextsmentioning
confidence: 99%
“…Families matter: the family is the primary social institution charged with the responsibility for rearing children to become productive members of society (Allen & Henderson, 2017;Seltzer, 2019). The family's emotional life is the interior arena for the transmission of values, attitudes, and behaviors that are deemed appropriate to the parents' social network (Buehler, 2020). Families are a container and a filter for communicating to the young what is valued by the parents' society, as well as how to think, feel, and behave as a member of that society.…”
mentioning
confidence: 99%